Towards Understanding Islamic Architecture - Omer, Spahic (Islamic Studies, 2008)
This article aims to discuss the meaning, functions and salient characteristics of Islamic architecture. The discussion will be divided into the following sections: (1) the meaning of Islamic architecture; (2) the object that Islamic architecture seeks to achieve; (3) the house and the mosque as examples of Islamic architecture; (4) pragmatism and Islamic architecture; (5) Islamic versus Muslim architecture; (6) the significance of Quṣayr ’Amrah as an example of early Muslim architecture. The article seeks to enhance the awareness, both of the professionals and general readership, as to the importance of correctly conceptualizing the theme of Islamic architecture, especially at the present when the signs of a Muslim cultural and civilizational re-awakening are becoming increasingly evident. The nature of the article, along with its content, methodology and conclusions, is conceptual and philosophical, rather than empirical